Influence of seed quality on plant growth and development - Chin, Hoong Fong (The International Seed Testing Association, 1976)
Seed quality plays a very influential role in plant growth and development. Various defects and disorders have detrimental effects such as slow seedling growth rate uneven maturity and reduced yield. Whereas high quality seeds which are graded selected and undamaged promote vigorous seedling growth an even stand establishment and maturity and most important higher yield. Agronomic practices and seed technology can be used to control plant growth and development for efficient crop production.